2D/0D graphene hybrids for visible-blind flexible UV photodetectors - Hiroyuki Tetsuka (Nature Portfolio, 2017)
Abstract Nitrogen-functionalized graphene quantum dots (NGQDs) are attractive building blocks for optoelectronic devices because of their exceptional tunable optical absorption and fluorescence properties. Here, we developed a high-performance flexible NGQD/graphene field-effect transistor (NGQD@GFET) hybrid ultraviolet (UV) photodetector, using dimethylamine-functionalized GQDs (NMe2-GQDs) with a large bandgap of ca. 3.3 eV. The NMe2-GQD@GFET photodetector exhibits high photoresponsivity and detectivity of ca. 1.5 × 104 A W–1 and ca. 5.5 × 1011 Jones, respectively, in the deep-UV region as short as 255 nm without application of a backgate voltage. The feasibility of these flexible UV photodetectors for practical application in flame alarms is also demonstrated.